Defining a Path Toward the Use of Fast-Scan Cyclic Voltammetry in Human Studies - Lucio Boschen, Suelen; Trevathan, James; Hara, Seth A.; Asp, Anders; Lujan, J. Luis (Frontiers in Neuroscience, 2021)
Fast Scan Cyclic Voltammetry (FSCV) has been used for decades as a neurochemical tool for in vivo detection of phasic changes in electroactive neurotransmitters in animal models. Recently, multiple research groups have initiated human neurochemical studies using FSCV or demonstrated interest in bringing FSCV into clinical use. However, there remain technical challenges that limit clinical implementation of FSCV by creating barriers to appropriate scientific rigor and patient safety. In order to progress with clinical FSCV, these limitations must be first addressed through 1) appropriate pre-clinical studies to ensure accurate measurement of neurotransmitters and 2) the application of a risk management framework to assess patient safety. The intent of this work is to bring awareness of the current issues associated with FSCV to the scientific, engineering, and clinical communities and encourage them to seek solutions or alternatives that ensure data accuracy, rigor and reproducibility, and patient safety.